1999
DOI: 10.1046/j.1464-410x.1999.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural‐fill urodynamics in chronically catheterized patients with spinal‐cord injury

Abstract: Objective To determine whether an indwelling catheter on free drainage provides a constantly low intravesical pressure in patients with a neuropathic bladder. Patients and methods Thirty patients with complete spinal‐cord injury (SCI) whose bladders were managed exclusively with an indwelling catheter were assessed urodynamically using natural‐fill urodynamics (ambulatory monitoring) while their catheters were left on free drainage. Their upper urinary tracts were assessed using plain X‐rays and ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…The higher rates of complications, both renal and lower urinary tract were attributed to a significant difference in bladder compliance in the catheter-dependent group. The emphasis on urodynamic pressures in chronically catheterized patients, and its impact on upper tract deterioration was underscored by the work of Jamil et al, 28 who reported on the urodynamics of 30 patients with SCI over 14.3 years, whose bladders were managed with an indwelling urethral catheter. They found that the indwelling catheters were not always associated with low intravessical pressure: detrusor contractions causing intravessical pressure rises greater than 40 cm H 2 O for up to 4.5 min were observed in 11/30 patients.…”
Section: Recent Analysis and Publicationsmentioning
confidence: 99%
“…The higher rates of complications, both renal and lower urinary tract were attributed to a significant difference in bladder compliance in the catheter-dependent group. The emphasis on urodynamic pressures in chronically catheterized patients, and its impact on upper tract deterioration was underscored by the work of Jamil et al, 28 who reported on the urodynamics of 30 patients with SCI over 14.3 years, whose bladders were managed with an indwelling urethral catheter. They found that the indwelling catheters were not always associated with low intravessical pressure: detrusor contractions causing intravessical pressure rises greater than 40 cm H 2 O for up to 4.5 min were observed in 11/30 patients.…”
Section: Recent Analysis and Publicationsmentioning
confidence: 99%
“…8 It is a common misconception that indwelling catheters protect against upper urinary tract deterioration, the intravesical pressure being the determining factor for this complication but not the intravesical volume or bladder capacity. 9 Neurogenic bladders can contract around the balloon of the indwelling catheter, leading to high intravesical pressure which can still cause vesico-ureteric reflux. Ascending infections with pyelonephritis as well as infectious bladder and kidney stones may, in addition, lead to loss of renal function.…”
Section: Natural History Of Neurogenic Bladder In Msmentioning
confidence: 99%
“…Natural-®ll urodynamics in chronically catheterised patients with spinal cord injury revealed that an indwelling catheter on free drainage was no guarantee of a constantly low intravesical pressure, and phasic bladder contractions occurred despite catheter drainage. 9 Detrusor contractions stimulated by the catheter, and consequent striated sphincter dyssynergia could predispose to urethro-vasal re¯ux of infected urine in a patient with an indwelling urinary catheter.…”
Section: Pathogenesis Of Xanthogranulomatous Epididymo-orchitis In Spmentioning
confidence: 99%